ANALISIS LITERATURE TENTANG STRATEGI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM YANG EFEKTIF DI ERA DIGITAL - Adnan, Adnan Syah Sitorus; Agus Alfaya Arif; Mizlan; Nurul Ainulhaq Tiara Putra (As-Sulthan Journal of Education, 2025)
The advancement of digital technology has brought significant changes to education, including Islamic Religious Education (PAI). This article aims to examine the transformation of PAI learning strategies in the digital era through a literature study, focusing on challenges, various effective strategies, as well as evaluation and implications of their implementation. The findings show that integrating traditional methods with digital technology, such as blended learning, flipped classroom, and interactive media, can enhance students’ motivation, engagement, and understanding of religious values. However, the success of these strategies depends on teachers’ readiness, infrastructure availability, and policy support. This article recommends improving teachers’ digital literacy, developing adaptive curricula, equalizing technology access, and utilizing interactive digital media to realize contextual and character-based PAI learning in the digital era.